Chemical constituents of Uncaria rhynchophylloides How and their chemotaxonomic significance. (August 2020) - Wang, Yun; Fang, Yin-Dong; Su, Jie-Li; Li, Rong-Sheng; Wang, Fei; Wang, Kou
Abstract: One undescribed 1, 4-diazaindan-type alkaloid, namely howlumine (1 ), along with seventeen known compounds, including a known analogue, agrocybenine (2 ), three iridoid glycosides (3 –5 ), four megastigmane glycosides (6 –9 ), two benzoic acid derivatives (10 –11 ), two phenylpropanoids (12 –13 ), and five flavonoids (14 –18 ), were isolated from the 95% EtOH extract of the aerial parts of Uncaria rhynchophylloides How. The structures of these compounds were elucidated by spectroscopic analyses. All compounds were isolated from this plant for the first time. Howlumine and agrocybenine represent the first report of 1, 4-diazaindan-type alkaloids from the genus Uncaria . Furthermore, the chemotaxonomic significance of the isolates was also discussed. Graphical abstract: Image 1 Highlights: A phytochemical investigation on Uncaria rhynchophylloides was conducted. Eighteen compounds including a new 1, 4-diazaindan-type alkaloid were obtained. All compounds were isolated from this plant for the first time. This is the first report of 1, 4-diazaindan-type alkaloids from the genus Uncaria. This finding provides new evidence for chemotaxonomic studies of the genus Uncaria.